PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN TEH WALINI DI INDUSTRI HILIR TEH PT. PERKEBUNAN NUSANTARA VIII BANDUNG - Tyas Abimanyu; Elpawati E; Achmad Tjachja Nugraha (AGRIBUSINESS JOURNAL, 2019)
PTPN VIII is an Indonesian state owned company concentrating in the field of agricultural / plantation. The company is located in West Java province. PTPN VIII had many commodities are grown and cultivated, including tea commodity. IHT PTPN VIII is expected to be able to see and take advantage of this opportunity for the development of tea production enterprises downstream. By because it's an improvement and evaluation of each line of the company should do. Ranging from human resources management, business strategy, finance, marketing, distribution, raw materials and so forth. Especially in terms of raw materials PTPN VIII IHT own advantages in this sector. Raw material supply is guaranteed because it has its own tea garden and the quality of tea used is also an excellent tea products. IHT PTPN VIII should be aware of this potential, especially coupled with increasing as well the tea industry competition IHT PTPN VIII should be better prepared to face competition to reform itself. The purpose of this research is (1) To determine whether the variables of quality of product, price, promotion and service quality partial effect on customer satisfaction Walini tea products in Downstream Tea PT.Perkebunan Nusantara VIII (2) To determine whether the variables of quality products , pricing, promotion and service quality simultaneous influence on consumer satisfaction Walini tea products in Downstream tea PT.Perkebunan Nusantara VIII. Based on the analysis, the majority of consumers are aged 26-35 years, sex permpuan, working as private employees, Knowing Walini tea product from a friend, itensitas purchase Not too often, the reason to buy a product because of the quality of the product. The quality of the product (X1), price (X2), promotion (X3), and quality of service (X4) partially affects consumer kepusan Walini tea in IHT PTPN VIII. This is evidenced by the variable t of product quality is 7.696 with a significant level of 0.000. Then t of the variable price is 2.375 with a significant level of 0,020. Then t of variable sale is 2,715 with a significant level of 0.008 and t of the variable quality of service is 3,387 to 0,001 signifakan level. The above data shows that significant value is generated each independent variable was below 0.05. Factors that affect customer satisfaction Walini tea at Tea Downstream Industry PT. Perkebunan Nusantara VIII with the most impact is the quality of the product and service quality, then price and finally the sale.